EXPERIMENTAL STUDY OF TERNARY FUEL BLENDS ON AN ASTM-CFR-CETANE ENGINE - Rocha, H. L.; Pinto, N. R.; Colaço, M. J.; Leiroz, A. J. K. (Revista de Engenharia Térmica, 2014)
This work analyses how ternary blends of biodiesel, anhydrous and hydrous ethanol, and diesel, in different proportions, behave regarding fuel emissions and combustion parameters. The determination of their cetane number, using an ASTM-CFR cetane research engine is also investigated. The base fuels used were 99,9% pure anhydrous ethanol, commercial diesel, which contains 5% of biodiesel in volume, biodiesel from soybean oil, and hydrous ethanol with 7% of water, in volume. The fuel blends were specified after a careful bibliography research. Five volume fractions of biodiesel (5, 10, 20, 60 and 100%, in volume) and four of ethanol (0, 5, 8 and 15%, also in volume) were used in this study. All blends have endured a mixture stability test prior to being burned, the ones with clear visual phase separation being eventually rejected. The results for the cetane number presented a clear decrease in its value as ethanol was added. Some blends with high ethanol content failed to provide the minimum cetane number for use in compression ignition engines according to the present Brazilian regulations. Concerning the emissions tests, carbon dioxide emissions showed a decreasing trend as the quantity of added ethanol raised. Carbon monoxide emissions, however, showed the opposite trend. The nitrogen oxides emissions presented an increase as more biodiesel was added to the blend. The conclusions as to the impact of changing ethanol’s volume in the blends were discussed taking in consideration important operational remarks. A final analysis was proposed in order to compare anhydrous and hydrous ethanol. A clear reduction in nitrogen oxides and carbon dioxide emissions was observed, with an almost identical value for the carbon monoxide emissions. Cetane number for the hydrous ethanol blend, however, suffered a decrease compared to the same blend with anhydrous ethanol.